2021
DOI: 10.35974/jpd.v4i2.2519
|View full text |Cite
|
Sign up to set email alerts
|

Meta Analisis: Pengaruh Model Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Matematis

Abstract: Untuk dapat meningkatkan kemampuan pemecahan masalah siswa salah satu caranya adalah dengan pemilihan model pembelajaran matematika yang tepat. Salah satu model pembelajaran yang dapat dipakai adalah model problem based learning. Tujuan penelitian ini adalah untuk menganalisis kembali pengaruh model problem based learning terhadap kemampuan pemecahan masalah matematis siswa dengan cara mereview, merangkum data dan menganalisis beberapa hasil penelitian yang sudah publish di google scholar sebanyak 14 artikel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
1
0
6
Order By: Relevance
“…Heterogeneity test results showed that the mean effect sizes did not differ across education levels (𝑄 = 0.075 and 𝑝 > 0.005). This is consistent with research conducted by (Yustinaningrum, 2021), who showed in his work that the impact of problem-based learning models has a tremendous impact on all educational levels, but (Yunita, Juandi, Hasanah, & Tamur, 2021), found that the effectiveness of project-based learning models was significantly more effective at the secondary education level compared to other educational levels. Mean effect size across education level groups from the effects of Creative Problem-Solving (CPS) learning models.…”
Section: Level Of Educationsupporting
confidence: 90%
“…Heterogeneity test results showed that the mean effect sizes did not differ across education levels (𝑄 = 0.075 and 𝑝 > 0.005). This is consistent with research conducted by (Yustinaningrum, 2021), who showed in his work that the impact of problem-based learning models has a tremendous impact on all educational levels, but (Yunita, Juandi, Hasanah, & Tamur, 2021), found that the effectiveness of project-based learning models was significantly more effective at the secondary education level compared to other educational levels. Mean effect size across education level groups from the effects of Creative Problem-Solving (CPS) learning models.…”
Section: Level Of Educationsupporting
confidence: 90%
“…For this reason, it is necessary to analyse, combine, and synthesise study results related to the application of ethnomathematical-based learning to describe in depth how much influence this learning has on increasing mathematical problemsolving abilities compared with the application of the ordinary learning. Yustinaningrum re-analyse the effect of the problem-based learning model on students' mathematical problem solving abilities (Yustinaningrum, 2021). Priska and Mawardi find the effect of the problem solving learning model and the problem posing learning model in improving critical thinking skills (Priska & Mawardi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Semua studi primer yang telah diidentifikasi diproses lebih lanjut dengan memberikan kode atau pengkodean pada studi primer. Pengkodean (coding) diperlukan untuk memudahkan pengumpulan dan analisis data sebagai salah satu syarat yang penting (Yustinaningrum, 2021). Nama peneliti, tahun, judul, dan sumber penelitian adalah variabel-variabel yang digunakan dalam membuat kode dan menghasilkan data yang dibutuhkan.…”
Section: Metodeunclassified